Ethno-Political Moves and Processes of Formation of the Identity of the Turkic Speakers in Iranian Azerbaijan in the XIX and Beginning of the XX centuries - Zohrabyan, Eduard (History and Culture, 2022)
In modern geopolitical processes, issues of ethnic identity occupy a significant place in the light of the formation of both interethnic and interstate military-political relations. In particular, in regions with a multi-ethnic characteristic, the issue of ethnic identity is of paramount importance. This often leads to conflicts. Among them, the factor of ethnic identity and self-identification of Iranian Azerbaijanis occupies a special role, which for a century has been manipulated by the state called Azerbaijan, which was formed in the Eastern Caucasus only in the 20th century.Based on factual material, the article presents the process of formation of the identity of Iranian Azerbaijanis and the differences from the similar process of ethnic identification of Turkic-speaking Muslims living in the Eastern Caucasus. Azerbaijanis are trying, through political manipulations, to substantiate territorial claims to Atrpatakan, the historical territory of northwestern Iran, the creation of "Great Azerbaijan" and the implementation of pan-Turkism programs.The Iranian Constitution does not attach much importance to the ethnic characteristics of the country's population, stating that "all Muslims constitute a single community." This fully applies to the Turkic-speaking Iranians. "The term 'ethnic Azerbaijanis' is used for propaganda purposes to emphasize the foreign character of some elements of Iranian society."In connection with the coverage of the issue, the geographical boundaries of the northwestern part of Iran, Atrpatakan, Caucasian Albania, linguistic problems in Iranian Azerbaijan, problems of ethno-political movements in Iran in the 19th and early 20th centuries and the formation of the ethnic identity of Azerbaijanis were considered.
Keywords: Atropatene; turkie tribes; Sout Azerbaijan; etnic groups; national identit; self-awareness; identification; nationalistic concepts; motherland; tribal affilattion; turkie azeri